International Noise Awareness Day — INAD Brazil 2022: INAD Brasil 2022 focused on childhood! - Fonseca, William D'Andrea; Kuniyoshi, Isabel Cristiane; Mello, Felipe Ramos de (Acústica e Vibrações, 2022)
<span data-sheets-root="1" data-sheets-value="{"1":2,"2":"INAD Brazil is the Brazilian branch of the International Noise Awareness Day (INAD) campaign, which aims to raise awareness about the impacts of noise on everyday life and public health. Each year, INAD Brazil presents a theme and a lema to highlight the importance of addressing the impacts of noise pollution in our country’s daily life and reality. Noise pollution is a global issue that affects humanity and the environment. This article describes the development of the Brazilian campaign for the year 2022. Initially, a brief presentation of INAD and its contextualization over the years with its activities in Brazil is provided, followed by a description of the theme, lema, and development of materials, as well as the activities carried out starting from INAD, which was celebrated on April 27, 2022. There is also a historical record of all the dates on which INAD took place. The text concludes with an announcement of the organization of INAD 2023."}" data-sheets-userformat="{"2":15357,"3":{"1":0},"5":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"6":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"7":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"8":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"10":1,"11":4,"12":0,"14":{"1":2,"2":0},"15":"Calibri","16":12}">INAD Brazil is the Brazilian branch of the International Noise Awareness Day (INAD) campaign, which aims to raise awareness about the impacts of noise on everyday life and public health. Each year, INAD Brazil presents a theme and a lema to highlight the importance of addressing the impacts of noise pollution in our country’s daily life and reality. Noise pollution is a global issue that affects humanity and the environment. This article describes the development of the Brazilian campaign for the year 2022. Initially, a brief presentation of INAD and its contextualization over the years with its activities in Brazil is provided, followed by a description of the theme, lema, and development of materials, as well as the activities carried out starting from INAD, which was celebrated on April 27, 2022. There is also a historical record of all the dates on which INAD took place. The text concludes with an announcement of the organization of INAD 2023.